The Construction of LGBT Criminalization in Qanun Jinayat Aceh: A Human Right and Islamic Sharia Perspective - Evi Damaika; Rahmad Syah Putra (Prodi Magister Ilmu Agama Islam, Pascasarjana UIN Ar-Raniry, 2026)
The Qanun Jinayat of Aceh, a regional criminal law rooted in Islamic Sharia, regulates same-sex acts through the categories of jarīmah liwāṭh and musāḥaqah. However, this legal construction raises critical issues, particularly in terms of normative Islamic law and human rights (HR). The main criticism targets its repressive and legalistic approach, which overlooks the sociological context and the identity dynamics of perpetrators. This neglects the principles of justice (al-'adl) and compassion (al-raḥmah) in maqāṣid al-sharī'ah, and fails to consider the legal capacity (ahliyyah al-wujūb) of offenders. Moreover, it does not cover the complexity of sexual identities such as transgender and bisexual, leading to potential legal inequality. This study aims to analyse the construction of LGBT criminalization in Qanun Jinayat Aceh, examine the foundations of critique, and propose a reformulation grounded in Sharia justice and human rights. The research employs a normative legal method with statutory, conceptual, and maqāṣid al-sharī'ah approaches, along with critical analysis of Islamic legal doctrines and HR principles. Data were collected through literature review of primary, secondary, and tertiary legal materials. The findings reveal that the criminalization framework is based on classical fiqh with a ta'zīr-based orientation to ḥifẓal-'irḍ (protection of dignity). Despite its repressive nature, there are signs of adaptation to maqāṣid al-sharī'ah, especially in protection and justice. The proposed reform includes: re-evaluation of ahliyyah al-wujūb for more proportional accountability; application of a double track system combining penal sanctions and rehabilitation; and development of contextual legal norms through a reconciliatory approach between Sharia and human rights.